Neoplastic and Nonneoplastic Lesions in Aging Mice of Unique and Common Inbred Strains Contribution to Modeling of Human Neoplastic Diseases. (May 2014) - Szymanska, H.; Lechowska-Piskorowska, J.; Krysiak, E.; Strzalkowska, A.; Unrug-Bielawska, K.; Grygalewicz, B.; Skurzak, H. M.; Pienkowska-Grela, B.; Gajewska, M.
The evaluation of spontaneous lesions in classical inbred strains of mice has become increasingly important because genetically engineered mice (GEMs) are created on these backgrounds. Novel inbred strains—genetically diverse from classic strains—are valuable both as a new background for GEM mice and to increase the genetic variation found in laboratory mice. Newly arising spontaneous genetic alterations in commonly used strains may also lead to new and valuable mouse models of disease. This report evaluates gross and histological lesions in relatively new, classic, and rarely explored mouse inbred strains. Pathological lesions of 1273 mice from 12 inbred strains (129S1/SvW, A.CA- H2 f /W, AKR/W, BALB/cW, BN/aW, C57BL/6 W, C57BL/10 W, C3H/W, C3H wad /W, CBA/W, DBA/2 W, and WOM/W) are reported. BN/aW, WOM/W, and C3H wad /W are novel inbred strains produced and maintained in the Department of Genetics and Laboratory Animal Breeding at the Center of Oncology, Warsaw, Poland. Both neoplastic and nonneoplastic lesions were examined. The prevalence of lung neoplasms was significantly higher in A.CA- H2 f /W (33.3%) and BALB/cW (33.8%) mice ( P < .01). The prevalence of liver neoplasms was significantly higher in the CBA/W strain ( P < .01). Mammary gland neoplasms arose at a greater frequency in C3H/W mice ( P < .01). The occurrence of uterine neoplasms was higher in DBA/W and 129S1/SvW mice. AKR/W and WOM/W mice developed T-cell lymphoblastic lymphoma with high frequency (110/121 [90.9%] and 159/175 [90.9%], respectively) before 1 year of age. The occurrence of nonneoplastic lesions in the kidneys of BN/aW mice was increased ( P < .01).